SIMULATION OF AN ACTIVE FRONT BUMPER SYSTEM FOR FRONTAL IMPACT PROTECTION - MAT NURI @ MD DIN, NUR RASHID; POKAAD, ALIF ZULFAKAR; HUDHA, DR KHISBULLAH; MOHD NASIR, MOHD ZAKARIA (2009)
In this paper, an active front bumper system is discussed on the effectiveness to reduce the jerk of a vehicle during collision. The mathematical model is done by using MATLAB 7.0 to simulate a collision between a pendulum and a vehicle installed with an active front bumper system. This study also presents the performance characteristics of a magnetorheological (MR) damper for controllable bumper in the vehicle system. One of promising candidate is the MR fluid undergoes significant instantaneous reversible changes in material characteristics when subjected to a magnetic field. The proposed damper is integrated with bellows to induce the flow motion and the motion is operated under flow mode. The parameter is change follow the situation or the behaviors of collision between pendulum and vehicle. If the situations are light and medium collision, the mass of pendulum will be change into 1/5 mass of vehicle and 3/5 mass of vehicle respectively. For heavy collision, the mass of pendulum is set same as mass of vehicle. In the simulation, the comparison of jerk and acceleration of the vehicle are done between an active front bumper system which use passive dampers and skyhook controller as its mechanism. Both mechanisms will test in modeling simulation for all type of collision.